Choroid plexus function in neurological homeostasis and disorders: The awakening of the circadian clocks and orexins. Issue 7 (July 2022) - Christensen, Jennaya; Li, Crystal; Mychasiuk, Richelle
As research regarding the role of circadian rhythms, sleep, and the orexinergic system in neurodegenerative diseases is growing, it is surprising that the choroid plexus (CP) remains underappreciated in this realm. Despite its extensive role in the regulation of circadian rhythms and orexinergic signalling, as well as acting as the primary conduit between cerebrospinal fluid (CSF) and the circulatory system, providing a mechanism by which toxic waste molecules can be removed from the brain, the CP has been largely unexplored in neurodegeneration. In this review, we explore the role of the CP in maintaining brain homeostasis and circadian rhythms, regulating CSF dynamics, and how these functions change across the lifespan, from development to senescence. In addition, we examine the relationship between the CP, orexinergic signalling, and the glymphatic system, highlighting gaps in the literature and areas that require immediate exploration. Finally, we assess current knowledge, including possible therapeutic strategies, regarding the role of the CP in neurological disorders, such as traumatic brain injury, migraine, Alzheimer's disease, and multiple sclerosis.